The sustainability of nuclear energy in Southeast Asia: opportunities and challenges - Cook, Alistair David Blair (2018)
ASEAN member states are moving towards diversifying their energy mix, reducing their over-dependence on fossil fuels, and exploring alternative energy sources such as nuclear energy to ensure that their energy supplies are secure, affordable and environmentally sustainable. Vietnam, Indonesia and Malaysia are the three ASEAN member states that are exploring the nuclear energy option. Although not all ASEAN member states presently have plans to build nuclear reactors, there are crucial reasons why the region has a vested interest in ensuring nuclear security, safety and safeguards (3S) in the region. First, any nuclear accident in the region would threaten public health and the environment through water and soil contamination as well as a radioactive plume which knows no borders. Second, the region’s fast-growing economies can be easily jeopardised by a nuclear accident as the operations of key economic sectors, including the supply chain, would be disrupted. Third, the region’s vital sea lanes, where radioactive materials will likely pass through, are not tightly guarded by maritime security forces. There is no guarantee that ASEAN member states will be able to fully secure all the radioactive materials and waste from their future NPPs and prevent terrorist threats. Hence, there is a need for ASEAN member states to start discussing possible regional mechanisms on the prevention of the trafficking of weapons of mass destruction and their means of delivery. Lastly, the region is home to the world’s major food producers and exporters. A nuclear accident can result in the radioactive contamination of farmlands and marine resources, disrupting the food supply chain. It is therefore in ASEAN member states’ interest if the region has collectively institutionalised nuclear safety and security, including the safe and secured transport of radioactive materials.